ADENOSQUAMOUS CELL CANCER OF THE PROSTATE: A CLINICAL CASE - A. A. Krasheninnikov; K. M. Nyushko; N. V. Vorobev; H. R. Maltzagova; B. Ya. Alekseev; N. N. Volchenko; A. B. Bruslinskaya; A. D. Kaprin (Южно-Российский онкологический журнал, 2020)
Prostate cancer (Pca) is the most common urogenital tumour in men. The most common histological form of prostate cancer is acinar adenocarcinoma. Rare morphological types of prostate cancer present an urgent clinical problem due to their aggressive course and the lack of rigorous standards for the management of such patients. Squamous and combined adenosquamous (ASC) prostate cancers are extremely rare histological forms of Pca, occurring in 0.5–1% of cases. The age of patients with these conditions varies from 52 to 79 years. Squamous cell and ASC cancers are among the most aggressive morphological types of prostate cancer. By the time of the diagnosis, most patients develop distant metastases, which are frequently localized in the lymph nodes and bones. In tumours of such a morphological structure, bone metastases are of osteolytic nature. The prognosis is unfavourable due to the rapid metastasis and development of the malignant process. The survival rate of patients averages 16 months after combined treatment. Only 20% of the patients with distant metastases at the time of diagnosis live longer than 6 months. In most cases, squamous cell Pca manifests itself through local symptoms, such as dysuria, bone pain and hematuria. The vast majority of patients have a normal level of prostate-specific antigen (PSA) in serum. Since ASC Pca is a fairly rare form of prostate cancer, no treatment standards have thus far been developed. Hormone therapy, chemotherapy and radiation therapy are believed to either be ineffective or show low efficacy in the treatment of ASC Pca. In cases where ASC Pca is localized, surgical treatment in the amount of radical prostatectomy, cystoprostatectomy or simultaneous surgical interventions with rectal resection can significantly extend the life of such patients. The article presents the clinical case of managing a patient with ASC Pca.